TINGKAT PENGETAHUAN PASIEN TENTANG PEMELIHARAAN KEBERSIHAN GIGI TIRUAN LEPASAN AKRILIK - Pocut Aya Sofya; Cut Fera Novita; Naztasia Murtilasari (Dentistry Faculty, 2016)
AbstractThe vertical dimension is height of the vertical face which can be measured based on assesment offacial height proportion. Facial height proportion divided into upper and lower. A normal of upper andlower facial height proportion is 50%. Dental malocclusion is a deviate relation between teeth and thiscan be affect the height of a person's face. Angle classification is the most classification whichcommonly used nowadays. Angle classify based on relation between maxilla and mandible first molar.A lower facial height proportion in molar relation class II division 2 is smaller than class I. This isbecause the molar relation class II division 2 has a deep bite as a result of upwards and forwardsmandibular growth. This research is a descriptive survey that aims to see ilustration facial heightproportion in molar relation class I and class II division 2 Angle in Student Faculty of Dentistry. Thesubjects of this study was consists of 133 subjects with molar relation class I and 6 subjects with molarrelation class II division 2 which selection using purposive sampling. Measuring facial heightproportion was used sliding digital caliper which measured from glabella to menton point. The result ofthis study shown that average upper facial height proportion in molar relation class I is 47,03% andclass II division 2 is 48,15%. While, average lower facial height proportion in molar relation class I is52,97% and class II division 2 is 51,84%.Keywords : vertical dimension, facial height proportion and molar relation